Main Regularities of Forming a New Delta of Rioni River - Papashvili, Irakli G.; Lebanidze, Becka V.; Lebanidze, Becka V.; Gvakharia, Vakhtang G.; Gvakharia, Vakhtang G. (Journals of Georgian Geophysical Society, 2017)
Based on natural measurements and geodetic references of old cartographic materials the new Rioni River delta (which was formed after the river diversion in 1939) development tendency was defined. A large two-arm delta was formed during a period of more than 60 years. The mentioned delta was developing along with a relative sea level rising, construction of a hydropower station on the river, and minimal sediment losses in the greater depths. Studies have shown that, despite the relative rise in the sea level by 0.53 cm, the coastline extension over a 13 km long section is continuous since 1939 until the present time. Construction of the hydropower plant and annual removal dredging of sediments from the approach channel of the port of Poti port slowed down the progradation, but general tendency of the coast development has not changed. We can therefore conclude that even in the face of global warming and associated sea level rise, not only the coastline maintenance in a stable condition is possible, but also its progradation in the case of the accumulative coasts, where there is no significant loss of beach-shaping sediments at greater depths and which are characterized by excessive intake of river sediments.